The Effect of Fountains and Vegetation on Temperature, Humidity and Thermal Comfort in Open Spaces with a Focus on Persian Garden: A Case Study of Kashan City - H. Kiani; J. Davtalab; M. Adib; A. Heidari (Iranica Journal of Energy and Environment)
Using renewable energy is an efficient method for addressing the drawbacks of utilizing fossil fuels. The study focuses on a multigeneration system that integrates PTC solar collector and geothermal energy, along with two ORC cycles, a single-effect absorption refrigeration cycle, a PEM electrolyzer, and a dryer. A TEG unit is utilized in the ORC cycles to increase power production. The system is analyzed from energy, exergy, and exergoeconomic perspectives using EES software. Parametric analysis is conducted to assess the impact of crucial parameters on the system's performance. The examination of overall results reveals that the energetic and exergetic efficiencies of the multigeneration system are 41.58 and 25.61%, respectively. The power generated by ORC1 turbine and ORC2 turbine are 461.9kW and 227.6kW, respectively. Introducing TEG units in place of condensers in the ORC cycles results in increased power production to 138.2kW and 328.2kW for ORC1 and ORC2 cycles. The energetic and exergetic COPs of the system are 0.8103 and 0.3484, respectively. Additionally, the multigeneration system is capable of producing 493.1 kg/day of hydrogen. Lastly, six different working fluids in the ORC cycle were investigated. It is demonstrated that among the 6 working fluids, n-pentane exhibited the best performance.